Sistema de informação geográfica na internet : sistema de monitorização de redes de abastecimento de água e saneamento - Rui Malhadas (2004)
In Portugal, water supply networks and sewerage systems have been improved over the last few years. This improvement of the infrastructure leads to an increase in the need to improve the quality of service. We have deployed a project to develop a geographic information system to store all information regarding the water supply network and sewerage system of Trás-o-Montes e Alto Douro. In this paper we present the functionalities and services of this system, as well as its architecture. Finally, some conclusions and future work will be presented.